2003
DOI: 10.1152/japplphysiol.00490.2003
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and reproducibility of spirometric response to ozone by gender and age

Abstract: Subjects were healthy nonsmoking men (n = 146) and women (n = 94) 18-60 yr old. Initially, each subject was exposed for 1.5 h to 0.42 ppm O3. Forty-seven individuals were later reexposed twice, 1 wk to several months apart, to 0.4 ppm O3. Intermittent exercise utilized in all exposures was adjusted to produce an O3 dose of 560 ppm x l/m2 body surface area. The post-O3 percent change in forced-expiratory volume in 1 s (delta%FEV1) decrements of young (18-35 yr) and middle-aged (36-60 yr) men and women differed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 29 publications
(34 reference statements)
1
51
0
Order By: Relevance
“…Some studies found a greater response in FEV 1 in female than in male subjects, whereas others found a comparable response between them, mostly after a short-term exposure to high-concentration ozone (27,28). For a prolonged exposure to low-concentration ozone, most studies report combined results of both males and females with no specific analysis for sex effects (6,7,15).…”
Section: Clean Airmentioning
confidence: 99%
“…Some studies found a greater response in FEV 1 in female than in male subjects, whereas others found a comparable response between them, mostly after a short-term exposure to high-concentration ozone (27,28). For a prolonged exposure to low-concentration ozone, most studies report combined results of both males and females with no specific analysis for sex effects (6,7,15).…”
Section: Clean Airmentioning
confidence: 99%
“…When the contaminant can be delivered in a sufficiently non-harmful way to allow human experimentation, studies typically focus on surrogate outcomes, such as spirometry measures of lung function, that are straightforward to measure but do not clearly map into realized health impairment, particularly for sensitive populations who are often omitted from such studies (Hazucha et al, 2003). Epidemiology, on the other hand, exploits real-world contamination to examine the relationship between environment and health in situ in an effort to better inform environmental policy.…”
Section: Introductionmentioning
confidence: 99%
“…The third question has been addressed. Gender does not appear to affect O 3 sensitivity (17), and physiological responses of young healthy women to O 3 exposure appear comparable to the response of young men (8).…”
Section: Discussionmentioning
confidence: 81%
“…Successive clinical research demonstrates decreases in forced expiratory volume in 1 s (FEV 1 ) and forced vital capacity in exercising healthy adults exposed to O 3 at ambient concentrations (8,10). Increased airway reactivity (5,7), as well as acute airway inflammation (18), have also been observed in healthy adults exposed to ambient O 3 concentrations during intermittent exercise.…”
mentioning
confidence: 99%